The Influences of Concentration Calcium Hydroxide (Ca(OH)2) and Immersion Time Upon the Various Chips Quality - Rahmi Mudia Alti; Ike Yuni Wulandari; Yoana Nurul Asri; Intan Cynara Valentina Putri (P2M Politeknik Pertanian Negeri Samarinda, 2023)
This research used the method of descriptive content analysis study. The analysis was done on any kind of scientific articles concerning to the usage of Ca(OH)2. Ca(OH)2 has used widely in any kind of liveness, such as the preservative on coconut sap and the eggs of purebred chicken, the preventer of browning on flour, the controller of rotten the base of the stem on the plants, as the alternative of the substance of mordant on textile ingredient, as the mixture of hampering the development to colony P. capsica diameter, as the mixture for treatment Orf traditionally, as the substance which helps in the process of separating weight metal waste industry. Ca(OH)2 is also used for the process of immersion to reduce the cyanide content inside cassava leaf, as the Thickener in increasing bio grease performance environmentally. Ca(OH)2 is the ingredient added to the processing of production on various chips in the stage of ingredient immersion. The addition of Ca(OH)2 has the purpose to repair chips' texture based on consumer wants. Ion calcium is by Ca(OH)2 having the reaction with the carboxyl group by pectin which is from tubers or fruits which are used as the main ingredient of chips. The Calcium hydroxide produced the gas CO2 which can form the pores in the chip surface, which had a good impact to have a texture crunchy chip produced. Another fixing of the texture, the addition of Ca(OH)2 has also the purpose to prevent the browning reaction until the appearance of chips becomes better. The effect of browning is going to appear because there is a reaction between the saccharides with the protein or amino acid. On some variously of chips ingredient, the function of Ca(OH)2 can omit the mucus, dissolve the mucus stuck, omit the itchy sensation, and simplify the process of development of chips when it is fried. The usage of concentration and the immersion time of Ca(OH)2 can turn into differences in every main ingredient for chips. It is occurred because the differences of tubers kind or fruit used, the natural water contains which was had to tubers/fruits, the method/the technique of immersion, and the temperature of immersion.